Inserção externa do sistema bancário brasileiro: análise sob a perspectiva da crise de 2008 - Lucarini, Fernando Dimas (2012)
The international insertion of banking systems comprises two streams the entry of foreign banks into the domestic markets and the expansion of domestic banks to foreign markets. This paper analyzes the latest internationalization process of the Brazilian banking sector in the perspective of the expansion of domestic banks abroad, focusing on the deepening of this phenomenon in the post-2008 crisis, being the crisis itself one of its determinants. Besides the crisis, the concentration of the domestic banking sector and the expansion of Brazilian companies abroad are identified as factors that corroborate this process. We also present a history of the internationalization of the Brazilian banking system from the 1970s, as well as the risks and opportunities that arise with such movements